PACULARITIES OF TRANSFERS OF EMPLOYEES:IMPACT ON THE ECONOMY OF UKRAINE - POLISHCHUK, YEVHENIIA; GARAPHONOVA, OLGA; ZHURAVEL, VALERII (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The potential for migration for development is closely linked to remittances, savings and investment intentions of migrant workers. However, the question of how the human, social and financial capital of migrant workers can be better used for the development of Ukraine is becoming increasingly important. What can the authorities do at the national, regional and local levels to increase the positive impact and remittances of migrant workers on Ukraine's future development?Based on the analysis results the following conclusions were drawn. Situation on the labor market of Ukraine, low level real wages, a decrease in the number of enterprises, rising unemployment, leads to the fact that Ukrainians are looking for work abroad. As a result, remittances from migrants are growing.The study is devoted to the analysis of remittances and migration processes in Ukraine. The data on the volume of private remittances of migrants are analyzed, the data on the distribution of the volume of remittances from abroad by channels of receipt are considered. The shares of private remittances to Ukraine by main countries were determined. The systems of transfers that are the most popular in Ukraine are compared. The structure of the volume of remittances from abroad by sources of formation is analyzed. An assessment of the impact of remittances and savings on the socio-economic development of Ukraine was made, as well as the provision of relevant data to support evidence-based recommendations to promote stability and sustainable socio-economic development in Ukraine.The consequences of migration processes are ambiguous, but their impact on the socio-economic and political development of Ukraine is growing. The degree of this influence largely depends on the effectiveness of the state's migration policy.
Keywords: money transfers; international payment systems; migration of migrants; money transfers of migrants; private transfers; NBU; money transfer channels; migrant worker